2022
DOI: 10.1371/journal.pone.0262757
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hypertension and diabetes comorbidity in a Korean population: A cross-sectional study

Abstract: Background Hypertension and diabetes are risk factors for severe cardiovascular disease and are prevalent comorbidities. No studies have examined the associations of various risk factors related to anthropometry, bone mineral density and body composition of specific body regions with hypertension and diabetes comorbidity (HDC). This study explored the association between HDC and various risk factors related to specific body regions. Method A total of 7,978 subjects (3,451 men and 4,527 women) aged ≥ 50 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 75 publications
2
9
0
Order By: Relevance
“…Our findings are consistent with these studies. A study in the Korean population also found a similar directional association 53 . More studies focused on the independent association between ES and hypertension and diabetes separately, especially in developing countries, and reported a positive association 34,54–57 .…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Our findings are consistent with these studies. A study in the Korean population also found a similar directional association 53 . More studies focused on the independent association between ES and hypertension and diabetes separately, especially in developing countries, and reported a positive association 34,54–57 .…”
Section: Discussionmentioning
confidence: 67%
“…A study in the Korean population also found a similar directional association. 53 More studies focused on the independent association between ES and hypertension and diabetes separately, especially in developing countries, and reported a positive association. 34 , 54 , 55 , 56 , 57 Obesity rates have risen with urbanization and gross domestic product growth, accompanied by shifts in diet and reduced activity.…”
Section: Discussionmentioning
confidence: 99%
“…(22) Contrarily, several studies have shown that the visual symptoms of CVS worsen when no breaks are taken. (23) Studies that have been done on the subject show that poor posture when sitting might increase musculoskeletal complaints. (24) Our research accurately outlined this public health concern and pinpointed the risk factors for computer vision sickness.…”
Section: Discussionmentioning
confidence: 99%
“…The association between comorbidity and body fat variables was more robust in women than in men aged fifty years and above. 22 In China, comorbid diabetes and hypertension were found to be higher among older persons, women, those with higher education, single and increased waist circumference. More importantly, comorbidity was significantly associated with higher risk of cardiovascular disease due to a synergistic and additive effect.…”
Section: Discussionmentioning
confidence: 99%